Hunger, Obesity, Public Policies, and Food-Based Dietary Guidelines: A Reflection Considering the Socio-Environmental World Context - Amorim, Alessandra; Barbosa, Ana de Holanda; Sobral, Paulo José do Amaral (Frontiers in Nutrition, 2022)
Nowadays, the world has been characterized by hunger, obesity, and food loss and waste. With the COVID-19 pandemic the food issue became more intense, serious and evident. Hunger demands urgent actions. Obesity levels have been raised and are removing health and quality of life from the population. Production planting practices and the food-supply chain are not necessarily ecologically friendly. Sustainability issues greatly intensify social problems. As well as food loss, waste and sustainability concerns, obesity and malnutrition are enhanced due to the lack of knowledge by the population. Processed food, packaging, and additives, despite still needing improvement, are essential to food security control. Nowadays, hunger is not due to insufficient agriculture practices, but rather to inequality and absence of adequate public policies. In a context of a certain abundance of food production and processing, the hunger scenario in contrast to food loss and waste is an ethical, social, moral and sustainable issue. In this context, a Food-Based Dietary Guideline (FBDG) can be an important public policy tool from health, nutrition, environmental and educational points of view. Despite the effort, the literature shows FBDGs can be better used to fulfil healthiness and sustainability purposes. In this scenario, elaboration/revision of the FBDG, adopting a clearer, simpler and a better suited communication strategy is essential. In this way, this article aims to discuss the importance of the FBDG as a public policy tool, not only regarding health issues but also communication strategies, production sustainability and humanitarian ones, which are crucial to FBDG´s efficiency.